Computational Investigation of the Thermal-Hydraulic Performance for Twisted Tape Enabled High Heat Flux Components. (3rd October 2017) - Clark, E.; Lumsdaine, A.; Ekici, K.; Ruggles, A.
Abstract: High heat flux thermal management is an important challenge for upcoming nuclear fusion and plasma physics experiments. The plasma facing components (PFCs) in devices such as ITER or Wendelstein 7-X (W7-X) will be subjected to extreme heat loads on the order of 10–20 MW/m 2 in the divertor region. The heat dissipation issue will become critical in this next generation of experiments, and active cooling will be necessary. The current state-of-the-art water cooled technologies can accommodate extreme heat fluxes and often utilize passive heat transfer enhancement techniques, such as swirl flow, to decrease the thermal loading on PFCs. Swirling flow is commonly induced with a twisted tape that is inserted into a circular tube. Twisted tape devices are planned for use in both W7-X and ITER. Computational modeling was performed to investigate the thermal-hydraulic performance for single-phase, turbulent flow of water through a twisted tape device. This study exploited the advantage of computational simulations by analyzing local flow information. It was shown that points of low wall shear stress corresponded to locations of low heat transfer coefficient and high surface temperatures. Thus, decreased wall shear stress could be an indicator for early burnout in twisted tape geometries. This analysis was the first step towards informing the design of twisted tape devices utilized in PFCs.